VALIDITY AND RELIABILITY ANALYSIS OF MULTIPLE CHOICE QUESTIONS ON THE QURAN AND HADITH IN THE SUBJECTS OF DA'WAH, KHUTBAH, AND TABLIG FOR GRADE XI AT MAN 1 MANDAILING NATAL - Febriansyah Siregar; Sri Wahyuni Khairani; Syamsiah Depalina Siregar (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the validity, reliability, difficulty level, and discriminatory power of multiple-choice questions on the material of Da'wah, Sermons, and Tablig for class XI at MAN 1 Mandailing Natal in the 2025/2026 academic year. The type of research used is descriptive quantitative, with 20 class XI students as subjects. Data were collected through a learning outcome test instrument, which was then analyzed using Microsoft Excel. Validity analysis was carried out using the Pearson Product Moment correlation formula, while reliability was calculated using the Cronbach Alpha formula. The results showed that out of 10 questions, there were 7 valid questions and 3 invalid questions. The reliability value (R₁₁) showed a very high level of consistency, so the instrument can be categorized as reliable. Analysis of the level of difficulty showed 30% of the questions were easy, 50% were moderate, and 20% were difficult, while the discriminatory power analysis showed 60% of the questions were categorized as good, 10% were sufficient, and 30% were poor. Overall, the test instrument is considered to be of good quality and suitable for use as an evaluation tool for Islamic Religious Education learning, although several items need to be revised to achieve more optimal construct suitability